نمذجة العلاقة بين مؤشرات الحجم الكلي للقطاع المصرفي والتنمية الاقتصادية في سورية باستخدام تحليل الارتباط القانوني المعياري - بشماني, شكيب; ديب, مازن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The development of any economic correlates with financing it, we aim in this research to modeling the relationship between the overall size banking sector indicators & economic development in Syria, Where on the indicators of overall size banking sector shape: (banking spread, banking assets ,banking deposits, banking credit), and the selected indicators to shape economic development are: (GDP per capita, expenses% GDP, investment% GDP, Trade openness% GDP) depending on data published by the central bank of Syria. By using model of standard canonical correlation analysis. As a result of this research, we found that there is a relationship of statistical significance between the overall size banking sector indicators & economic development indicators in Syria. Show that the variables (GDP per capita, investment% GDP) most closely related to variables (number of banking branches, deposits % GDP, credit to the private sector % GDP, population per bank branch), and the variables (expenses% GDP, trade openness% GDP) most closely related to variables (credit to the private sector % total deposits, banking assets % GDP, credit to the private sector % GDP) and the variables (expenses% GDP, investment% GDP) most closely related to variable (banking assets % GDP). هدف هذا البحث الى نمذجة العلاقة بين مؤشرات الحجم الكلي للقطاع المصرفي والتنمية الاقتصادية في سورية, حيث تمثلت مؤشرات الحجم الكلي للقطاع المصرفي بـ: ( الانتشار المصرفي, الموجودات المصرفية, الودائع المصرفية والائتمان المصرفي), والمتغيرات المختارة لتمثيل التنمية الاقتصادية ( نصيب الفرد من GDP, النفقات كنسبة من GDP, الاستثمارات كنسبة من GDP, والانفتاح التجاري كنسبة من GDP) اعتماداً على البيانات التي ينشرها مصرف سورية المركزي, باستخدام اسلوب تحليل الارتباط القانوني المعياري, وتوصلنا نتيجة لهذا البحث إلى أنّه توجد علاقة ذات دلالة احصائية بين مؤشّرات الحجم الكلي للقطاع المصرفي ومؤشرات التنمية الاقتصادية في سورية, وتبيّن أنّ متغيري (نصيب الفرد من GDP, الاستثمارات% GDP) أشد ارتباطاً بمتغيّرات (عدد الفروع المصرفية, الودائع% GDP, الائتمان المقدم للقطاع الخاص% GDP, عدد السكان لكل فرع مصرفي), وأنّ متغيري (النفقات% GDP, الانفتاح التجاري% GDP) أشد ارتباطاً بـ: (الائتمان المقدم للقطاع الخاص% اجمالي الودائع, الموجودات المصرفية% GDP, الائتمان المقدم للقطاع الخاص% GDP), ومتغيري (النفقات% GDP, الاستثمارات% GDP) أشد ارتباطاً بـ: (الموجودات المصرفية% GDP).